Legal Justice Discourse on Land Rights in the Indonesian Constitution - Try Widiyono (Publindo Akademika, 2022)
As the Constitution observes, the purpose of the establishment of the Indonesian state is to achieve dignity and justice. One form of this justice is land rights. Until now, the land law is still a complicated discussion and often raises the pros and cons. This article aims to examine how the concept of land ownership in Indonesia is based on the state constitution. The method used in this research is normative-juridical law research with a descriptive-analytical approach. Under the Constitution, the state is not the owner but the land use and ownership regulator. The state’s function is to regulate the allocation and use of land as regulated in the Basic Agrarian Law (BAL). Thus, the law must be able to minimize the negative excesses of the development of land conflicts by creating the legal norms needed to protect people who may be harmed. The law must be able to control business transactions and economic development without having to leave the function of law to provide a sense of security and justice.